2008
DOI: 10.1089/aid.2008.0095
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Subtype B, Multiple Circulating Recombinant Forms and Unique Recombinants of HIV Type 1 in an MSM Cohort in China

Abstract: To study HIV-1 genetic diversity among HIV-positive men who have sex with men (MSM) in China, a cohort consisting of HIV-positive MSM was established in 2005 and was monitored every 2 years. In 2007, 44 HIVpositiveMSM subjects were genotyped, and the results showed HIV-1 subtype B decreased from 77.5% to41.9%, but non-B subtypes increased rapidly represented by CRF01_AE from 3.7% to 30.2% compared to 2005.In addition, one case of CRF07_BC was first identified in this population, which mainly circulated among H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
2
36
0
1
Order By: Relevance
“…In contrast, China recently witnessed a dramatic shift in genotype distribution from subtype B to CRF01_AE among MSM. (16)(17)(18). The rise of CRF01_AE infections among MSM has also been reported in other regions in China, including Liaoning (northeastern) (19), Jiangsu (eastern) provinces (10), Shijiazhuang, the capital city of Hebei (north-central) (20), and Zhengzhou, the capital city of Henan (Central) (21).…”
mentioning
confidence: 64%
“…In contrast, China recently witnessed a dramatic shift in genotype distribution from subtype B to CRF01_AE among MSM. (16)(17)(18). The rise of CRF01_AE infections among MSM has also been reported in other regions in China, including Liaoning (northeastern) (19), Jiangsu (eastern) provinces (10), Shijiazhuang, the capital city of Hebei (north-central) (20), and Zhengzhou, the capital city of Henan (Central) (21).…”
mentioning
confidence: 64%
“…Recently, however, MSM is the risk group associated with the most rapid increases in HIV infections within China, and studies note HIV-1 strains of different subtypes and CRFs. [38][39][40][41][42] In cities in northern China CRF01_AE infection in MSM is more common than subtype B, 24,[43][44][45] with similar trends in Beijing, Fujian, Guizho, Guandong, Guanxi, Hebei, Hong Kong, Hunan, Jiangsu, Jianxi, Shanghai, and Yunnan. CRF07_BC has recently been identified in young MSM and in some cities exceeds the prevalence of CRF01_AE infection (unpublished data).…”
Section: Hiv-1 Molecular Epidemiologymentioning
confidence: 92%
“…It is well known that subtype B=, CRF07_BC, CRF08_BC, and CRF01_AE are the major HIV-1 genotypes associated with particular risk populations in China (2,25,26,31). Reports about China in recent years showed that multiple HIV-1 subtypes, including subtype B, CRF01_AE, and CRF07_BC, were coepidemic in the population of MSM (18,32,33).…”
mentioning
confidence: 99%
“…CRF01_AE, which was the dominant strain in the sexual-risk population (34), seems to have played a more and more important role within the population of MSM. The percentage of CRF01_AE has been increasing recently and has exceeded that of subtype B, the previously dominant strain, in different cities (10,14,18,31,32). In addition, Chen et al reported that the time of the epidemic of the most recent common ancestor (tMRCA) of CRF01_AE in Hong Kong was in the mid1990s (3).…”
mentioning
confidence: 99%